Structural Properties and Bandgap Energy of Ga-doped Garnet-type Li7La3Zr2O12 (LLZO) Solid Electrolyte Depending on Sintering Atmosphere - Saran, Sevda (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2025)
Developing solid-state batteries for higher energy densities and safety has been a popular research subject in recent years. Since their first report, Li7La3Zr2O12 (LLZO) solid electrolytes have attracted extended attention due to their high ionic conductivity, chemical stability, and wide electrochemical window. Although LLZO fulfills all the requirements for high energy density and a longer lifespan, its intrinsic electronic conductivity accelerates the Li dendrite growth short-circuiting the battery. In this study, we have applied air and oxygen sintering atmospheres to prepare two types of Ga-doped LLZO pellets, to identify the effect of sintering atmospheres on the physical properties such as crystal phase, ionic conductivity, roughness, and electronic band gap energy (Eg). Both the crystal structures were found to be in cubic phase with a relatively small amount of secondary phase impurities. On the other hand, the oxygen-sintered sample showed better properties with high ionic conductivity of 1.04x10-4 Scm-1, lower surface root-mean-square roughness of 0.1833 µm, and a relative density of 90.5%. Furthermore, the electronic indirect band gap energy of the oxygen-sintered sample was larger, Eg=5.77 eV, which is desired for lower electrical conductivity. It is important to note that the precise determination of Eg values of powders would be erroneous through Ultraviolet-Visible (UV-Vis) absorption spectroscopy due to the scattering effects of solids. So, to the best of our knowledge, for the first time, this study reports Eg values of oxygen and air-sintered LLZO determined by the Kubelka-Munk model on Ultraviolet-Visible-Near Infra-Red (UV-Vis-NIR) diffuse reflectance spectroscopy.